DESAIN DIDAKTIS BERORIENTASI SUSTAINABILITY PADA TOPIK PENGOLAHAN AIR UNTUK MENGEMBANGKAN LITERASI SAINS MAHASISWA CALON GURU KIMIA - Cita Rachmi Andini, - (2023)
This study aims to design a sustainability-oriented didactical design on water treatment topic to overcome learning obstacleand develop science literacy of preservice chemistry teacher. The didactical design was designed using Didactical Design Research which includes the didactical situation (before, during and after learning), prediction of the responses of preservice chemistry teacher that appear and anticipation of educators. This research was conducted on preservice chemistry teacher at one of the State Universities in Bandung. The instruments used were test questions, expert validation sheets, and video recording transcript analysis sheets. Based on pre-learning analysis, most of the students' initial science literacy was in the low category and students' understanding was still weak on several concepts including: (a) water pollution; (b) stages of water treatment process; (c) the process of coagulation mechanism; (d) the difference between synthetic coagulants and natural coagulants (e) water turdibity; (f) coagulant advantages based on structure; (g) the concept of sustainability in water treatment using natural coagulants. The results of the analysis of learning obstaclewere used to design a didactic design which was then validated by experts. The design of didactic design development is organized on didactic situation, response prediction, and didactic and pedagogical anticipation. After the design was applied to learning, information was obtained that most of the responses that appeared were in accordance with those designed by educators and the final results of science literacy and understanding of preservice chemistry teacher had developed. Based on this, it is known that sustainability-oriented didactical design on the topic of water treatment using natural coagulants has the potential to develop science literacy and overcome learning obstacleof preservice chemistry teacher.